(untitled) (Journal of actual problems of jurisprudence, 2021)
The article is devoted to the actualization of the problems of national-state identity in the modern globalizing world and the basic political, legal and cultural grounds for the formation of national-state identity in Kazakhstan. The purpose of this work is to study the political, legal and culturological foundations of the national-state identity of the Republic of Kazakhstan to determine its (identity) character in the context of the need to solve modernizing super-tasks facing all states of the world wishing to be subjects, not objects in the modern geopolitical space. The author notes the particular importance of preserving the institution of the state as the main guarantor of ensuring and protecting all types of identity from the level of the individual to the level of the state, including human identity in general, in the context of the transition of the world mega-society to a new level of technological development – «Industry-4.0». In the context of modern trends in the formation of integral research methods, this work combines different approaches: a systematic approach to the sphere of politics by the famous American sociologist, founder of the school of structural functionalism Talcott Parsons, the concept of waves of democratization by S. Huntington, the paradigm of late start societies by Alexander Gershenkron. The idea is substantiated that there are no “cultural breaks” in Kazakhstan and, taking into account modern demographic factors, the ethnic composition of the population, we can talk about the national-state identity in the Republic of Kazakhstan as having an integral character and constructive potential for progressive development. The scientific and practical significance of this work lies in the fact that the national-state identity of the Republic of Kazakhstan is considered not only in the context of its integral nature, but also in the critical discourse of the problems of archaization, marginalization, and imitation imperative. The study of the political, legal and culturological foundations of the national-state identity of the Republic of Kazakhstan, the identification of the integral nature of this identity will become the theoretical basis for developing a strategy and tactics for the progressive development of our country to solve the necessary modernization super tasks. Key words: national-state identity, political and legal foundations, cultural grounds, institution of the state, the Constitution of the Republic of Kazakhstan.